2009
DOI: 10.3201/eid1505.090159
|View full text |Cite
|
Sign up to set email alerts
|

Cowpox Virus Transmission from Pet Rats to Humans, Germany

Abstract: We describe a cluster of cowpox virus (CPXV) infections in humans that occurred near Munich, Germany, around the beginning of 2009. Previously, only sporadic reports of CPXV infections in humans after direct contact with various animals had been published. This outbreak involved pet rats from the same litter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 12 publications
2
114
0
3
Order By: Relevance
“…CPXV infections are presently limited to Europe and Asia. Human CPXV infections acquired from pet rats or other pet or zoo animals are reported in increasing number ( [Baxby et al, 1979], [Baxby et al, 1994], [Pilaski et al, 1986], [Vorou et al, 2008] and [Campe et al, 2009]) and the number of animal species susceptible to CPXV is increasing similarly. Field and experimental studies have indicated that CPXV has a broad host range and maintains a reservoir in wild rodents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPXV infections are presently limited to Europe and Asia. Human CPXV infections acquired from pet rats or other pet or zoo animals are reported in increasing number ( [Baxby et al, 1979], [Baxby et al, 1994], [Pilaski et al, 1986], [Vorou et al, 2008] and [Campe et al, 2009]) and the number of animal species susceptible to CPXV is increasing similarly. Field and experimental studies have indicated that CPXV has a broad host range and maintains a reservoir in wild rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the virus is often isolated from domestic cats, which should be regarded as a potential source of infection in urban areas ( [Baxby et al, 1979], [Chantrey et al, 1999] and [Hazel et al, 2000]). The majority of human CPXV and MPXV infections have a mild course, leading to localized, often selflimiting skin lesions with low morbidity (Campe et al, 2009). However, hospitalization of CPXVinfected individuals is reported and immunosuppressed individuals are at particular risk of developing severe complications, including disseminated infection and death ( [Eis-Hübinger et al, 1990] and [Czerny et al, 1991]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, in the region of Krefeld, Germany, six patients were affected with one case of severe eye involvement and another case with pulmonary infections [6]. In 2009, an outbreak of ulcero-cutaneous cowpox was reported in greater Munich area, Germany, with five affected patients who had bought rats form the same litter [18]. In 2011, eight patients were affected in Munich, Germany [7].…”
Section: Discussionmentioning
confidence: 99%
“…как следствие, к настоящему времени человеческая популяция практически не имеет коллективного про-тивооспенного иммунитета и является беззащитной не только перед возможным инфицированием други-ми близкородственными ортопоксвирусами, такими как вирусы оспы обезьян (воо) или оспы коров, природным резервуаром которых являются мелкие грызуны, но и перед заражением вно в результате теракта или возникновения вируса в природе путем эволюции зоонозных ортопоксвирусов [39,40]. в последние годы отмечается увеличение числа заре-гистрированных случаев заболевания людей оспой коров [6,7,10,18,22,32], вакциноподобным заболе-ванием [4, 42 ,47, 50] и оспой обезьян [24,33,37,38]. вакцинопрофилактика остается единственным эф-фективным инструментом сдерживания возрастаю-щей угрозы ортопоксвирусных инфекций человека.…”
unclassified